Biodegradable PEI modified complex micelles as gene carriers with tunable gene transfection efficiency for ECs. Issue 5 (11th January 2016) - Lv, Juan; Yang, Jing; Hao, Xuefang; Ren, Xiangkui; Feng, Yakai; Zhang, Wencheng
Abstract : In recent years, gene therapy has evoked an increasing interest in clinical treatments of coronary diseases because it is a potential strategy to realize rapid endothelialization of artificial vascular grafts. Abstract : In recent years, gene therapy has evoked an increasing interest in clinical treatments of coronary diseases because it is a potential strategy to realize rapid endothelialization of artificial vascular grafts. The balance of high transfection efficiency and low cytotoxicity of nonviral gene carriers is an important issue to be solved. In this study, we aim to establish a gene delivery system offering an elegant way to tune the transfection activity and cytotoxicity. Biodegradable complex micelles were prepared from polyethylenimine- b -poly(lactide- co -3( S )-methyl-morpholine-2, 5-dione)- b -polyethylenimine (PEI- b -PLMD- b -PEI) and methoxy-poly(ethylene glycol)- b -poly(lactide- co -3( S )-methyl-morpholine-2, 5-dione) (mPEG- b -PLMD) copolymers by a co-assembly method. Then the ZNF580 gene plasmid (pDNA) was encapsulated into the complex micelles. The hydrodynamic size and zeta potential of these complex micelles and micelles/pDNA complexes indicated that they were feasible for use in cellular uptake and gene transfection. As expected, the transfection efficiency and cytotoxicity of these micelles/pDNA complexes could be conveniently tuned by changing the mass ratio of mPEG- b -PLMD to PEI- b -PLMD- b -PEI (3/1, 2/2, 1/3 and 0/4) in the mixed mPEG/PEI shell. The transfection efficiency increased as the mass ratio of mPEG- b -PLMD/PEI- b -PLMD- b -PEI decreased from 3/1 to 0/4, while the cytotoxicity showed an opposite tendency. Moreover, ZNF580 protein expression determined by Western blot analysis and the migration of transfected endothelial cells (ECs) by wound healing assay were consistent with the result of transfection efficiency. All these results indicated that the co-assembled complex micelles could act as suitable gene carriers with tunable gene transfection efficiency and cytotoxicity, which should have great potential for the transfection of vascular ECs.